English Dominance and Linguistic Justice in Contemporary Higher Education Systems - Laila Husna Zahra (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study aimed to explore how English dominance shapes the conditions of linguistic justice in contemporary higher education systems. It sought to understand how English functions not only as a communicative medium but also as an ideological force that structures power, recognition, and epistemic legitimacy within multilingual and postcolonial academic contexts. Subjects and Methods: The research employed a qualitative interpretive design grounded in critical sociolinguistics and discourse analysis. Data were collected from institutional policy documents and semi-structured interviews with eighteen participants, including lecturers, students, and policy makers from three universities representing international, bilingual, and local-language contexts. Thematic and critical discourse analyses were used to interpret the relationship between institutional structures, linguistic ideologies, and personal experiences of inclusion and exclusion. Results: The findings revealed that English functions simultaneously as a resource of opportunity and a mechanism of exclusion. Institutional policies framed English as the marker of academic prestige, while local languages were symbolically preserved but materially marginalized. Participants described emotional fatigue, linguistic insecurity, and identity tension in navigating English-dominant systems, yet some also developed bilingual strategies that embodied acts of resistance and linguistic agency. Conclusions: English dominance in higher education perpetuates epistemic inequality by privileging Anglo-normative linguistic standards while undermining local knowledge systems. Achieving linguistic justice requires more than policy inclusion; it demands an epistemological shift that values all languages as equal vehicles of academic thought. Only through such plural recognition can higher education sustain intellectual diversity and moral equity.